ANALYSIS ON EXPORT COMPETITIVENESS AND FACTORS AFFECTING OF NATURAL RUBBER EXPORT PRICE IN INDONESIA - Putri Daulika; Ke-Chung Peng; Nuhfil Hanani (Agricultural Socio-Economics Journal, 2020)
Rubber is one of Indonesia's leading plantation commodities that is oriented to the international market with export destination countries to several countries. Rubber provides a positive contribution to the economy because it generates foreign exchange for the country. This study aims to analyze (1) the factors that influence the price of Indonesian natural rubber exports and (2) the position of Indonesia's rubber competitiveness in comparative and international competitive advantages. This study uses time-series data is from 1995 to 2017. Data were analyzed using multiple linear regression for influence factors the price of Indonesian natural rubber exports, while to analyze the position competitiveness of Indonesian natural rubber that is by using a revealed comparative advantage (RCA), and competitive advantage by using the Trade Specialization Index approach (TSI). The results of this study show (1) the factor that significantly affects the price of Indonesia's natural rubber exports are international rubber prices, exchange rate, and domestic consumption. (2) Based on competitiveness analysis, through Revealed Comparative Advantage (RCA) indicate that the competitiveness of Indonesia's natural rubber exports on the international market has a comparative advantage seen from 1995-2017 with an average value of RCA> 1 which is equal to 1.01. While the competitive advantage for the competitiveness of Indonesian rubber exports is at the maturation stage. This condition occurs because the value of the Trade Specialization Index (TSI) approaches 1, which is 0.98.